Factors Related with Dengue Hemorrhagic Fever Incidence in 2008-2017 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
Abstract The number of cases of DHF in Indonesia from year to year tends to increase and the area of ​​spread is increasingly widespread. The incidence of DHF in the city of Semarang over the past 10 years (2008-2017) experienced fluctuations. The purpose of this study was to determine the factors that correlated with data on DHF incidents in Semarang City in 2008-2017. This research is a quantitative descriptive study with correlation study by using a type of time series analysis design. Data analysis was performed in univariate, bivariate by using Spearman correlation test, and multivariate by using Multiple Linear Regression test. The results showed that rainfall (r = 0.201; p = 0.028) and population density (r = -0.761; p = 0,000) correlated with DHF incidence data. Air temperature (r = -0,150; p = 0,103) and air humidity (r = 0,171; p = 0,062) did not correlate with DHF incident data. Rainfall, air temperature, air humidity, and population density had an effect of 62.8% on DHF incident data and the most influential factor is air humidity. The conclusion of this study is that rainfall and population density correlate with DHF incidence data, the most influential factor on DHF incidence data is air humidity. Abstrak Jumlah kasus DBD di Indonesia dari tahun ke tahun cenderung meningkat dan daerah penyebarannya semakin luas. Angka kejadian DBD di Kota Semarang selama 10 tahun terakhir (2008-2017) mengalami fluktuasi. Tujuan dari penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan data kejadian DBD di Kota Semarang tahun 2008-2017. Penelitian ini merupakan penelitian kuantitatif deskriptif dengan studi korelasi menggunakan jenis desain analisis seri waktu. Analisis data dilakukan secara univariat, bivariat menggunakan uji korelasi Spearman, dan multivariat menggunakan uji Regresi Linier Berganda. Hasil menunjukkan bahwa curah hujan (r=0,201; p=0,028) dan kepadatan penduduk (r=-0,761; p=0,000) berhubungan dengan data kejadian DBD. Suhu udara (r=-0,150; p=0,103) dan kelembaban udara (r=0,171; p=0,062) tidak berhubungan dengan data kejadian DBD. Curah hujan, suhu udara, kelembaban udara, dan kepadatan penduduk berpengaruh sebesar 62,8% terhadap data kejadian DBD dan faktor yang paling berpengaruh adalah kelembaban udara. Simpulan dari penelitian ini adalah curah hujan dan kepadatan penduduk berhubungan dengan data kejadian DBD, faktor yang paling berpengaruh terhadap data kejadian DBD adalah kelembaban udara.